Solve for the g-variable: 15 - g = 23 - 2g
First: combine "like" terms > combine the "g" variables on one side (left)---add "2g" by both sides (when you move a term to the opposite side, always use the opposite sign) ...
15 - g + 2g = 23 - 2g + 2g
15 - g + 2g = 23
15 + g
Sec: subtract 15 from both sides...
15 - 15 + g = 23 - 15
g = 23 - 15
g = 8
2007-02-09 05:18:30
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
Rather plainly
G = 8
and you verify this:
In the left hand side for g=8 you get 15 - 8 = 7
In the right hand side when g=8 you get 23-2(8) =23-16=7
So letting g=8 DOES make the left side = the right side.
i.e. when g=8 the original equation becomes a true statement. Thus g=8 is a valid solution.
One failing that people make is to presume the solution is valid and then generate a true statement from the presumption; that is not the correct approach.
Notice if I presume 2=3, then 3=2 and if I add equals to equals I get 5=5, which says nothing about the truth of the original equation
2007-02-09 13:41:31
·
answer #2
·
answered by answerING 6
·
0⤊
0⤋
The basic idea is if you do the same things to both sides of the equation, it is still true. So to solve, want g terms on one side and other terms on the other side.
So start by adding 2g to both sides:
15 - g + 2g = 23 - 2g + 2g = 23
Now subtract 15 to both sides:
15+ g - 15 = 23 -15
g = 8
2007-02-09 13:16:38
·
answer #3
·
answered by bozo 4
·
0⤊
0⤋
You want to get the variable on one side of the = sign, and the real numbers on the other side. Add 2g to both sides of the equation. This gives you 15+g=23. Next subtract 15 from both sides. g=8. When you do the same thing to both sides of an equation, the equation is still equal.
2007-02-09 13:15:53
·
answer #4
·
answered by beachrat808 2
·
0⤊
1⤋
given, 15-g=23-2g
now -g+2g=23-15,
or 2g-g=8,
or g = 8 answer
2007-02-09 13:26:21
·
answer #5
·
answered by rahul kaushik 1
·
0⤊
0⤋
Its pretty easy.
There are two sides to the equation, 15-g and 23-2g.
g is a letter representing the same value on each side. 2g means twice the value of g.
What you need to do to solve it is find the value of g. To do this, you need to move all of the 'g' values to one side of the equation.
Because we have an equation, as long as we do the same thing to both sides, it will still work.
Our first problem is that all of the 'g' values we have are negative (subtracted), which can make things look trickier than they are. So, to resolve this, we need to add '2g' to both sides;
15-g+2g = 23-2g+2g
If we now put all of the 'g' values on each side together, we get;
15+g = 23
The -g and 2g on the left have cancelled down to a single 'g' value.
The 2g and -2g on the right cancel out altogether.
So, now we have just a single value of g, on the left hand side. If we can get it on its own, we have completed the equation. So, we consider what we need to remove from the left hand side to get g on its own.
We therefore subtract 15 from each side of the equation.
15+g-15 = 23-15
We can now use the numbers to cancel each other out. This gives us;
g=8
Woo-hoo, congratulations!
2007-02-09 13:20:15
·
answer #6
·
answered by Whateverandeverandamen 2
·
0⤊
1⤋
The answer is g=8. Because 15 - 8 = 23 - 16 (which is 2 x 8)
2007-02-09 13:17:37
·
answer #7
·
answered by Hotsauce 4
·
0⤊
1⤋
Simplify the equation-
start by adding g to both sides to leave you with
15 = 23-g or written another way 23 - ? = 15
from that you can work out that g = 8.
2007-02-09 13:20:29
·
answer #8
·
answered by M M 4
·
0⤊
0⤋
8
2007-02-09 13:15:30
·
answer #9
·
answered by whodeyflya 6
·
0⤊
2⤋
Add -15 to both sides.
-g = 8 -2g
Add 2g to both sides
g = 8
2007-02-09 13:17:55
·
answer #10
·
answered by Ron H 6
·
0⤊
0⤋